Exploring Services Science First International Conference, IESS 2010, Geneva, Switzerland, February 17-19, 2010, Revised Papers - Morin, Jean-Henry; Ralyté, Jolita; Snene, Mehdi (Lecture Notes in Business Information Processing,, 2010)
The discipline of Services Science, introduced by IBM in 2002, has emerged and matured in a true transdisciplinary atmosphere. Encompassing disciplines not only in management and engineering, it also draws from disciplines such as social and cog- tive sciences, law, ethics, economics etc. to address the theoretical and practical - pects of the challenging services industry and its economy. Services Science leverages methods, results and knowledge stemming from these disciplines towards the development of its own concepts, methods, techniques and approaches thus creating the basis for true trans-disciplinary gatherings and the p- duction of transdisciplinary results. Services Science is building a concrete framework for transdisciplinary purposes. IESS1. 0 - the First International Conference on Exploring Services Science - was the first international conference held in Europe in this domain. The conference took place during February 17-19, 2010 in Geneva, Switzerland. The goal of the conf- ence was to build upon the growing community to further study and understand this emerging discipline. Academics, researchers and practitioners of all disciplines were invited to contribute their results and approaches to Services Science in a tra- disciplinary setting. In order to achieve the best possible mix of disciplines and their representation, the conference call for papers was structured around transdisciplinary service research topics including service innovation, service exploration, service - sign, service engineering, and service sustainability, and around more disciplinary oriented service contexts such as: sectors and services, IT and services, foundations of services science, and governance and management.